Marion Nicoll Silence and Alchemy - Davis, Ann; Herbert, Elizabeth (Art in Profile, 2013)
Marion Nicoll (1909-1985) is a widely acknowledged and important founder of Alberta art and certainly one of a dedicated few that brought abstraction into practice in the province. Her life and career is a story of determination, of dedication to her vision regardless of professional or personal challenges. Nicoll became the first woman instructor hired at the Provincial Institute of Art and Technology (now the Alberta College of Art and Design) - and although limited to teaching craft and design, she became a significant mentor for generations of artists. Contributions by Ann Davis, Elizabeth Herbert, and Jennifer Salahub.